ANALISIS PELAKSANAAN PENGAMANAN DI SECURITY CHECK POINT (SCP) 2 TERHADAP TINGKAT KEAMANAN PENUMPANG DI BANDAR UDARA INTERNASIONAL SULTAN HASANUDDIN MAKASSAR - Moch. Afrizal Ramly; Kukuh Tri Prasetyo; Sudrajat (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Sultan Hasanuddin International Airport Makassar as one of the airports that become the gateway of air transportation from eastern Indonesia to the west. The airport is experiencing an increase in passengers every year. When the author conducted the research during On Job Training at Sultan Hasanuddin International Airport Makassar, the author noticed that there was a queue of passengers during rush hour at Security Check Point 2. This is due to a limited line of inspection. As a passenger check center before boarding, Security Check Point 2 needs special handling or attention. So the author concluded the need for a review related to security checks at Security Check Point 2 that has a security impact on passengers. Methodology in use in this research is quantitative descriptive research method, namely by describing the current situation in the research object. Data obtained from live observation, library review, and kueisioner. The results of the research that has been done by the author prove that there is still the need for the addition of inspection lines and inspection equipment at Security Check Point 2 of Sultan Hasanuddin International Airport Makassar. This is done so that there is no buildup of passengers on the inspection line and Avsec personnel can work to the maximum. Then it can smoothen and give a safe impression to passengers.